Mathematics teachers’ initial implementation of a digital tool package - Erfjord, Ingvald (NOMAD Nordic Studies in Mathematics Education, 2016)
The study reported in this paper was situated within developmental research and concerns teachers’ initial implementation of a digital tool in mathematics teaching. The paper illuminates two types of implementation processes, and takes an activity theory perspective in the discussion of reasons and the types of issues experienced and addressed in the implementation processes. Using activity theory parlance it is argued that although the teachers appeared to have rather similar objects for the implementation, there were great differences in teachers’ goals and the kinds of issues dealt with in the implementation processes. The schools’ organisation, internal collaboration within each school and how the external requirements for mathematics teaching, such as a curriculum and examination standards, were approached, played a significant role in the different implementation processes.